Influence of the entrepreneur's social identity on business performance through effectuation - Marina Estrada de la Cruz; Antonio J. Verdú Jover; Jose M. Gómez Gras (European Research on Management and Business Economics (ERMBE), 2018)
The business founder's social identity is crucial to explaining his or her behaviour and attitude in business decision-making. Drawing on three types of entrepreneurial social identity identified by Fauchart and Gruber (2011), this study examines how social identities influence the entrepreneur's way of managing his/her firm and its consequences for business performance. Based on a survey of newly created firms, the results support the conclusion that effectuation channels the effects of specific identities – Darwinian and missionary – on business performance.
Keywords: M13; L26; M10; 650; University entrepreneurs; Business performance; Effectuation; Social identity